Quality Control Management in Processed Beef Production in MSMEs (PT XYZ) - Rangga Mahardika; Nadia Aurin Azmi; Berliana Oktavia; Muhamad Giofadli Nugraha; Yogi Gunawan; Fatul Rahman; Amadea Selma Agnia Elfath; Riska Novintri (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study focuses on the design and implementation of a quality control management system for the production of rendang at PT XYZ, a local SME. The objective of this research is to analyze and design an integrated quality control system using Statistical Process Control (SPC) tools, including P-control charts and Fishbone diagrams. Data collection was carried out through direct observation, interviews with the owner, and documentation of production records from February 2025. The study found that although the production process was within statistical control limits, there were still variations in product quality, especially in taste and aroma, as well as packaging issues. This research emphasizes the importance of a structured quality management system to enhance product consistency and reduce defects. Recommendations for improvement include formalizing standard operating procedures (SOPs), conducting regular worker training, and adopting modern equipment to ensure more uniform production conditions. The findings of this study provide practical insights for SMEs in the food processing industry to improve product quality and operational efficiency, while also contributing to the development of quality management systems in the local food production industry